Systematology, theoretical psychology and the epistemology of psychology: a framework for analyzing the systems of psychology - Catriel Fierro; Ornella Bruna; Laureano Brisuela Blume (Interacciones)
A specific theoretical and methodological context for a teaching proposal on psychological systems based on meta-theoretical analysis parameters and specific meta-scientific models is presented, with the aim of repositioning systems of psychology undergraduate courses, and their intellectual and procedural exercises, in the subsystem of the epistemology of the psychology. Firstly, the place of schools and systems in psychology's development is characterized. Secondly, international, regional and local debates that have taken place in the last decades regarding systematology as curricular content in psychologists' education are described. Thirdly, we describe the field of Anglo-Saxon theoretical psychology, where the comparative study of psychological systems is a central part of the field. In such a programmatic context, systematology, far from being an enunciative exercise of the concepts of the various psychological systems, constitutes a metatheoretical discipline at the metascience, thus consisting in an epistemological exercise. We conclude both on the centrality of psychological systems in psychologists' education, and on the need for concrete pronouncements on the diverse variables that make the curricular concretion of systematology. Such conclusions will be taken up and developed in an upcoming work that synthesizes a curricular and programmatic proposal for the teaching of psychological systems